Incorporation of QoS in network mobility (NEMO) network - Hussien, Loay Faisal; Hassan Abdalla Hashim, Aisha; El-Hazary, Ismail; Hassan, Wan Haslina; Habaebi, Mohamed Hadi (IJCSNS, 2013)
The contemporary Internet that we have been using today is based on Best-Effort (BE) service only, where packets are assigned and forwarded with the same priority. The BE service is acceptable only for traditional Internet applications like e-mail, web browsing and file transfer. However, it is not adequate for the applications like video conferencing, voice over IP (VoIP), and Video on Demand (VoD), which require high bandwidth, low delay and delay variation. Obviously, with the emergence of new real-time applications and Quality of Service (QoS) requirements, the Best Effort service becomes insufficient. Therefore, the Internet community has developed a number of new technologies to provide QoS in the Internet such as IntServ, DiffServ and MPLS. The differentiated service (DiffServ) is the most important distinct technology due to its simplicity and scalability benefits. It has been endorsed by Internet Engineering Task Force (IETF) to satisfy the requirements of new real-time applications. Internet Protocol was not designed taking into account mobility of users and terminals. In few years later, the IETF has developed protocols such as Mobile IPv4 (MIP) and Mobile IPv6 (MIPv6) for supporting seamless connectivity to mobile hosts. Mobile IPv6 is considered one of the important host mobility protocols, which was defined more in (RFC 3775 and RFC 6275). Network mobility basic support protocol (RFC 3963) is an extension of Mobile IPv6. It has been endorsed by Internet Engineering Task Force (IETF) to allow every single node in the mobile network to be reachable and connectable to the Internet while the network itself is moving around. Ultimately, this paper aims to propose and develop a new scheme to enhance QoS within NEMO environment. Key words: Mobile IPv6, NEMO, Quality of Service, DiffServ.